2013
DOI: 10.1016/j.joep.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Expressed likelihood as motivator: Creating value through engaging what’s real

Abstract: Our research tested two predictions regarding how likelihood can have motivational effects as a function of how a probability is expressed. We predicted that describing the probability of a future event that could be either A or B using the language of high likelihood (“80% A”) rather than low likelihood (“20% B”), i.e., high rather than low expressed likelihood, would make a present activity more real and engaging, as long as the future event had properties relevant to the present activity. We also predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The latter, intriguing possibility would point more to the "phenomenal" quality of truth motivation. Rather than being just a subjective assessment of one's overall effectiveness in this motivational domain, truth motivation could be an experience of the world becoming more real and coherent, and thus more valuable (see Higgins, Franks, Pavarini, Sehnert, & Manley, 2012, for some evidence of this), as well as, more specifically, an experience of a stronger motivation for solving puzzles and problems that disrupt that coher-ence (whether your own or others' problems). The present research suggests that this experience is relevant not only in that it gradually brings focus to one's personal goals, but also because it embeds the experiencer in a world that places demands on one's actions and character to right wrongs they encounter.…”
Section: Discussionmentioning
confidence: 99%
“…The latter, intriguing possibility would point more to the "phenomenal" quality of truth motivation. Rather than being just a subjective assessment of one's overall effectiveness in this motivational domain, truth motivation could be an experience of the world becoming more real and coherent, and thus more valuable (see Higgins, Franks, Pavarini, Sehnert, & Manley, 2012, for some evidence of this), as well as, more specifically, an experience of a stronger motivation for solving puzzles and problems that disrupt that coher-ence (whether your own or others' problems). The present research suggests that this experience is relevant not only in that it gradually brings focus to one's personal goals, but also because it embeds the experiencer in a world that places demands on one's actions and character to right wrongs they encounter.…”
Section: Discussionmentioning
confidence: 99%
“…This is not to say that Brehm's theory of emotional intensity is the same as regulatory engagement theory. Brehm's theory identifies other factors that contribute to emotional intensity that are not part of regulatory engagement theory and regulatory engagement theory postulates additional sources of engagement strength other than opposing interfering forces, such as regulatory fit (see Higgins 2006), use of proper means , and expressions of likelihood that make future events more real (Higgins et al 2013). Nonetheless, there are implications of Brehm's theory that are applicable to regulatory engagement theory as well, such as his theory highlighting an important boundary condition to intensification from opposition-that the interfering force could become too strong to be overcome (i.e., too strong to oppose), which would produce disengagement and de-intensify the evaluative responses.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Indeed, the value effect in such scarcity situations could also be reduced by people not experiencing the objects as being real, as when a threatened, almost extinct species has become so rare that it feels almost imaginary, like the extinct dodo bird. In this regard, it should also be noted that expressing the low likelihood that the almost extinct species will survive-in the hope that this will make the need to help the species seem more urgent-could actually make the species seem less real and thus less valuable (see Higgins et al 2013). These possibilities should also be examined in future research.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higgins, Franks, Pavarini, Sehnert, & Manley, 2013). Moreover, previous research has found that individuals increase the strength with which they engage in their goal pursuit under regulatory fit (Hong & Lee, 2007;Uskul et al, 2008).…”
Section: Regulatory Fit Feeling Right and Regulatory Engagementmentioning
confidence: 98%